Language Premium Myth or Fact: Evidence from Migrant Workers of Guangdong, China - Xiahai Wei; Tony Fang; Yang Jiao; Jiahui Li (Institute of Labor Economics (IZA), 2019)
Using unique matched employer-employee data from China, we discover that migrant workers in the manufacturing industry who are proficient in the local dialect earn lower wages than those who are not. We also find that workers with better dialect skills are more likely to settle for lower wages in exchange for social insurance. We hypothesize that they are doing so in the hope of obtaining permanent residency and household registration status (hukou) in the host city where they work. Further tests show that the phenomenon of "exchanging wages for social insurance participation" is more pronounced among workers employed in smaller enterprises. Moreover, migrant workers with better language skills have a stronger desire to stay in the host city. Our conclusions are robust to different specifications, even after addressing the endogeneity issue for language acquisition. The present study provides a new perspective on the impact of language fluency on social integration among migrants, one of the most disadvantaged groups in developing countries.
Keywords: J32; J61; R23; 330; wages; language ability; dialect; social insurance; migrants; China